2018
DOI: 10.1038/s41598-018-33527-3
|View full text |Cite
|
Sign up to set email alerts
|

Transposon mutagenesis screen in mice identifies TM9SF2 as a novel colorectal cancer oncogene

Abstract: New therapeutic targets for advanced colorectal cancer (CRC) are critically needed. Our laboratory recently performed an insertional mutagenesis screen in mice to identify novel CRC driver genes and, thus, potential drug targets. Here, we define Transmembrane 9 Superfamily 2 (TM9SF2) as a novel CRC oncogene. TM9SF2 is an understudied protein, belonging to a well conserved protein family characterized by their nine putative transmembrane domains. Based on our transposon screen we found that TM9SF2 is a candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…RNAs derived from SH4 with (#4 and #5) or without (Mock; two samples) B4GALNT1 over-expression were analyzed by RNA sequencing as described in ref. [76][77][78] . Quality tested with Bioanalyzer 2100 (Agilent Technologies, USA).…”
Section: In Vivo Tumorigenesismentioning
confidence: 99%
“…RNAs derived from SH4 with (#4 and #5) or without (Mock; two samples) B4GALNT1 over-expression were analyzed by RNA sequencing as described in ref. [76][77][78] . Quality tested with Bioanalyzer 2100 (Agilent Technologies, USA).…”
Section: In Vivo Tumorigenesismentioning
confidence: 99%
“…DMRs associated with PFOA were also annotated to NR1H2, involved in lipid homeostasis and inflammation; and RPTOR, part of the mTOR complex that regulates cell growth in response to nutrient availability. Other genes that were associated with multiple PFAS include RNF39, a gene within the major histocompatibility complex class 1 region on chromosome 6 associated with early synaptic plasticity and previously linked with multiple sclerosis (Maltby et al 2017); RASL11B, a widely expressed gene with proposed roles in inflammation and arteriosclerosis (Stolle et al 2007); and TM9SF2, encoding a transmembrane protein and reported to be a colorectal cancer oncogene (Clark et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…TM9SF2 is an evolutionarily conserved transmembrane protein and has been identified as a glycolipid-regulating factor and a novel colorectal cancer oncogene 14,26 . However, the function of TM9SF2 in tumorigenesis and progression of PAAD still needs to be delineated.…”
Section: Discussionmentioning
confidence: 99%
“…In our current study, we identified that LINC01232 positively regulated its nearby gene transmembrane 9 superfamily member 2 (TM9SF2). A recent study has indicated that TM9SF2 acts as a novel oncogene in colorectal cancer 14 . Nevertheless, the participation of TM9SF2 in pancreatic carcinoma progression is vague.…”
Section: Introductionmentioning
confidence: 99%